PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN MULTIMEDIA DALAM PENINGKATAN PEMBELAJARAN IPA PADA SISWA KELAS V SDN WONOTORO TAHUN AJARAN 2014/1015 - Budi Atmoko, Didik (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Implementation of Problem Based Learning (PBL) Model In Improving Natural Science Learning Using Multimedia For The Fifth Grade Students Of SDN Wonotoro In Academic Year 2014/2015. The objectives of this research to improve natural science learning about water cycle for the fifth grade students. This research is a Collaborative Classroom Action Research conducted for 3 cycles with phases of planning, action, observation, and reflection. Subjects were fifth grade students of SDN Wonotoro totaling 22 students. Data collection techniques were observation, interview, and test. Validity of data applied triangulation of source and techniques. The analysis of data consisting of data reduction, data description, and conclusion. The conclusion of this research is the implementation of the Problem Based Learning (PBL) models with multimedia can improve natural science learning for fifth grade students in SDN Wonotoro. Keywords: Problem Based Learning (PBL), multimedia, natural science Abstrak : Penggunaan Model Problem Based Learning (PBL) dengan Multimedia dalam Peningkatan Pembelajaran IPA pada Siswa Kelas V SDN Wonotoro Tahun Ajaran 2014/2015. Tujuan penelitian ini untuk meningkatkan pembelajaran IPA tentang daur air pada siswa kelas V. Penelitian ini merupakan Penelitian Tindakan Kelas Kolaboratif yang dilaksanakan dalam 3 siklus dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian adalah siswa kelas V SDN Wonotoro yang berjumlah 22 siswa. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan tes. Validitas data menggunakan triangulasi sumber dan triangulasi teknik. Analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Kesimpulan penelitian ini adalah penggunaan model Problem Based Learning (PBL) dengan multimedia dapat meningkatkan pembelajaran IPA pada siswa kelas V SDN Wonotoro. Kata Kunci: Problem Based Learning (PBL), multimedia, IPA